Wide hybridization in Rapeseed-Mustard: Wide hybridization in Rapeseed-Mustard - ARUN KUMAR; HS MEENA; BL MEENA; HARIOM SHARMA; REEMA RANI; PRASHANT YADAV; VV SINGH; PK RAI (Journal of Oilseeds Research, 2023)
The Brassicas are an important group of crops in India yielding oils and many vegetables. For improving cultivated brassicas, the distant relatives are of considerable value. Wide hybridization is the way which could combine the valuable features of parental species into the hybrid. Crosses among Brassicaspecies viz., B. juncea (AABB, 2n = 36), B. Carinata (BBCC, 2n = 34), B. napus (AACC, 2n = 38), B. campestris (AA, 2n = 20), wild relative of cultivated species B. fruticulosa (2n = 4x=32, FFFF), and B. tournefortii (2n=20, TT) were attempted with the objective to find out crossability among them, analyse chromosome association in inter-specific hybrids, generate genetic variability and combine desirable characters in a targeted genotypes/species.